THE EFFECT OF PATIENT TRUST AND HOSPITAL FACILITIES ON IN-PATIENT SATISFACTION AT HASANUDDIN UNIVERSITY HOSPITAL - Nurmalawati (Paulus Journal of Accounting (PJA), 2023)
The hospital is an integral part of a social and health organization with the function of providing complete services, curing disease and disease prevention to the community. It is undeniable that the community has an assessment decision on the quality and performance of services at the hospital. Therefore, hospitals must pay attention to patient satisfaction in order to maintain patient trust and as stronghold in facing global competition. Patient satisfaction can be influenced by several factors including patient trust and hospital facilities. This study aims to analyze the effect of patient trust and hospital facilities on inpatient satisfaction. The research method uses a cross-sectional study design. The research began in March-April 2023 at the Hasanuddin University Hospital. The number of samples used were 96 patients taken using purposive sampling technique. Data collection was measured using a questionnaire with a Likert scale which was filled in directly by the respondents. Data were analyzed using the Chi-Square test and Multiple Logistic Regression test. The test results show that there is an effect of patient trust and hospital facilities on inpatient satisfaction at Hasanuddin University Hospital. Therefore, the hospital should maintain what has supported patient satisfaction and trust, and should repair or provide facilities that patients complain about so that they are able to support patient trust and satisfaction at Hasanuddin University Hospital.